Age, Sex, Health Insurance, and Race Associated With Increased Rate of Emergent Pediatric Gastrointestinal Procedures. Issue 6 (June 2017) - Andrews, Ashley; Franklin, Linda; Rush, Natasha; Witts, Robin; Blanco, David; Pall, Harpreet
ABSTRACT: Objectives: Few studies have examined the role health disparities play in pediatric gastrointestinal (GI) procedures. We hypothesized that health disparity factors affect whether patients undergo an emergent versus nonemergent GI procedure. The aims were to characterize the existing pediatric population undergoing GI procedures at our institution and assess specific risk factors associated with emergent versus nonemergent care. Methods: We retrospectively reviewed the medical records of 2110 patients undergoing GI procedures from January 2012 to December 2014. Emergent procedures were performed on an urgent inpatient basis. All other procedures were considered nonemergent. Health disparity factors analyzed included age, sex, insurance type, race, and language. Logistic regression analysis identified the odds of undergoing emergent procedures for each factor. Results: Most study patients were boys (58.2%), primarily insured by Medicaid (63.8%), white (44.0%), and spoke English (91.7%). Ten percent of all patients had an emergent procedure. Logistic regression analysis showed significant odds ratios ( P value) for ages 18 years older (2.16, 0.003), females (0.62, 0.001), commercial insurance users (0.49, <0.0001), African Americans (1.94, <0.0001), and other race (1.72, 0.039). Conclusions: Health disparities in age, sex, insurance, and race appear to exist in this pediatric population undergoing GI procedures. Patients older than 18 years, African Americans, and other races were significantly more likely to have an emergent procedure. Girls and commercial insurance users were significantly less likely to have an emergent procedure. More research is necessary to understand why these relations exist and how to establish appropriate interventions.